Comparative study and hybrid modeling approach with POD for convective drying performance of porous moist object with multi-impinging jet and channel flow configurations - Selimefendigil, Fatih; Coban, Seda Ozcan; Öztop, Hakan Fehmi (Pergamon-Elsevier Science Ltd, 2022)
Comparative studies for convective drying performance of a porous moist object in channel flow and with multiimpinging jet flow configuration are performed with finite element method. The analysis is conducted for different Re numbers (between 100 and 300), hot inlet temperature (between 50 and 80 degrees C), porous moist object size (between w and 3.5w) and jet flow arrangement parameters in unsteady configuration for times up to 1000 min. Flow re-circulations and isotherms within the channel and jet flow arrangement vary with Re number, size of the object and jet flow parameters. The moisture reduction (MR) becomes higher for the jet flow arrangement and higher Re number while at Re = 300, its value is 59.66%. Increasing the hot air inlet temperate resulted in increment of MR by about 17.5% for multi-impinging jet flow configuration while it is only 10% for channel flow arrangement. There is nearly 20% deviation in the MR value when cases with porous moist object with the lowest and highest size are compared. The vertical distance between the inlet jets to the porous object becomes more effective on the convective drying performance when compared to horizontal distance in between the jets while the MR values reduces from 61% to 48.5% when configurations with lowest and highest vertical distances are considered. An efficient hybrid model with proper orthogonal decomposition (POD) is proposed for efficient computations of convective drying. The computational cost for one case is reduced from 1.3 h for fully coupled high fidelity computational fluid dynamics simulations to 0.1 h with the proposed hybrid approach. The method is also flexible to handle complex external flow configurations and will be more efficient in 3D simulation case.
Keywords: Convective drying; Porous moist object; Jet impingement; FEM; POD